A Review of Polarization of light, and its applications - Kanishk; Bhatia, Sanjana (Innovative Research Thoughts, 2018)
Controlling and manipulating the polarization of light is crucial for many optical applications.Optical designs frequently focus on the wavelength and intensity of light, often neglecting its polarization. Polarization is an important property of light that affects even those optical systems that do not explicitly depends on it. The polarization of light plays a major role in the focusing of laser beams, affects the cut-off wavelengths of waveguides, and can be important to prevent unwanted signal losses. Polarization measurements are important in many metrology applications such as stress analysis in glass or plastic, pharmaceutical ingredient analysis, and biological microscopy. Different polarizations of light can also be absorbed to different depths by materials, an essential property for LCD screens, 3D movies, and your glare-reducing sunglasses. This paper is a review article of Polarization, shedding light on the ways to manipulate and control polarization of the incident light and diversified applications of this wonderful optical phenomenon.